Give and take - Napoli, Donna Jo, 1948-; Klementz-Harte, Lauren, 1961- (New York : Aladdin Paperbacks, 2000)
A little angel has to think carefully and work hard as he tries to lead Dinah to understanding the values of generosity and honesty
"Ages 7-10"--cover p. [4]
Keywords: Angels -- Fiction; Generosity -- Fiction; Honesty -- Fiction